2014
DOI: 10.1371/journal.pone.0087674
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Exposure Prophylaxis for the Prevention of HIV Infection in High Risk Populations: A Meta-Analysis of Randomized Controlled Trials

Abstract: BackgroundNearly ten randomized controlled trials (RCTs) of pre-exposure prophylaxis (PrEP) have been completed or are ongoing worldwide to evaluate the effectiveness of PrEP in HIV transmission among HIV-uninfected high risk populations. The purpose of this study was to evaluate the role of PrEP to prevent HIV transmission through a Mata-analysis.MethodsA comprehensive computerized literature search was carried out in PubMed, EMbase, Ovid, Web of Science, Science Direct, Wan Fang, CNKI and related websites to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 35 publications
0
43
0
2
Order By: Relevance
“…139 Early PrEP trials in Cambodia failed to launch due to ethical, political, and logistical concerns raised by civil society leaders during 2004, [140][141][142] and initiation of the Bangkok Tenofovir PrEP study was delayed for several years. 143 Two clinical trials of oral PrEP for HIV-negative individuals conducted in Thailand showed a reduction in HIV acquisition in MSM 144 and in PWID 143 ( Results of the PROUD study and of the on-demand (before and after sexual intercourse) ''Ipergay'' PrEP study showed a relative reduction of 86% in the incidence of HIV acquisition among MSM.…”
Section: Preexposure Prophylaxis (Prep) and Microbicidesmentioning
confidence: 99%
“…139 Early PrEP trials in Cambodia failed to launch due to ethical, political, and logistical concerns raised by civil society leaders during 2004, [140][141][142] and initiation of the Bangkok Tenofovir PrEP study was delayed for several years. 143 Two clinical trials of oral PrEP for HIV-negative individuals conducted in Thailand showed a reduction in HIV acquisition in MSM 144 and in PWID 143 ( Results of the PROUD study and of the on-demand (before and after sexual intercourse) ''Ipergay'' PrEP study showed a relative reduction of 86% in the incidence of HIV acquisition among MSM.…”
Section: Preexposure Prophylaxis (Prep) and Microbicidesmentioning
confidence: 99%
“…Developing HIV prevention options that women can use therefore remains a global concern, given the soaring rates of HIV infection among women. Preexposure prophylaxis (PrEP), in which HIV uninfected persons with ongoing HIV risk use antiretroviral medications as chemoprophylaxis against sexual HIV acquisition, is a promising new HIV prevention strategy [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…40,41 A recent meta-analysis of seven PrEP randomized controlled trials demonstrated an overall risk reduction of 47% confirming previous findings. 42,43 PrEP research is evolving with 17 ongoing studies 44 assessing the efficacy of PrEP in new populations (adolescents at high risk and transgender), development of new drug delivery systems, formulations with longer half-life, and open-label extension of prior efficacy trials. 45 The approval of Truvada (oral tenofovir disoproxyl fumarate and emtricitabine) for PrEP by the US Food and Drug Administration (FDA) in 2012 46 and the release of guidelines by WHO [47][48][49] and CDC 50,51 recommending PrEP for certain populations represented a significant biomedical Contribute to the design of the scientific agenda, manufacture and supply products to be tested in humans and work on access and licensure with national public health and regulatory authorities Media Newspapers, TV, radio, internet, newsletters…”
Section: Pre-exposure Prophylaxismentioning
confidence: 99%